Applying an intersectionality lens to the theoretical domains framework: a tool for thinking about how intersecting social identities and structures of power influence behaviour - Etherington, Cole; Rodrigues, Isabel Braganca; Giangregorio, Lora; Graham, Ian D.; Hoens, Alison M.; Kasperavicius, Danielle; Kelly, Christine; Moore, Julia E.; Ponzano, Matteo; Presseau, Justin; Sibley, Kathryn M.; Straus, Sharon (BMC medical research methodology, 2020)
Background A key component of the implementation process is identifying potential barriers and facilitators that need to be addressed. The Theoretical Domains Framework (TDF) is one of the most commonly used frameworks for this purpose. When applying the TDF, it is critical to understand the context in which behaviours occur. Intersectionality, which accounts for the interface between social identity factors (e.g. age, gender) and structures of power (e.g. ageism, sexism), offers a novel approach to understanding how context shapes individual decision-making and behaviour. We aimed to develop a tool to be used alongside applications of the TDF to incorporate an intersectionality lens when identifying implementation barriers and enablers. Methods An interdisciplinary Framework Committee ( n = 17) prioritized the TDF as one of three models, theories, and frameworks (MTFs) to enhance with an intersectional lens through a modified Delphi approach. In collaboration with the wider Framework Committee, a subgroup considered all 14 TDF domains and iteratively developed recommendations for incorporating intersectionality considerations within the TDF and its domains. An iterative approach aimed at building consensus was used to finalize recommendations. Results Consensus on how to apply an intersectionality lens to the TDF was achieved after 12 rounds of revision. Two overarching considerations for using the intersectionality alongside the TDF were developed by the group as well as two to four prompts for each TDF domain to guide interview topic guides. Considerations and prompts were designed to assist users to reflect on how individual identities and structures of power may play a role in barriers and facilitators to behaviour change and subsequent intervention implementation. Conclusions Through an expert-consensus approach, we developed a tool for applying an intersectionality lens alongside the TDF. Considering the role of intersecting social factors when identifying barriers and facilitators to implementing research evidence may result in more targeted and effective interventions that better reflect the realities of those involved.